The Dangerous Consumption of Hazardous Snacks and Independent Smart AcupresureTraining as Intelligence Improvements Students in Mlajah Elementary Schools Bangkalan Madura - Suminar, Ervi; Widiharti; Sari, Levi Tina; Renityas, Nevy Norma (Journal of Community Service for Health, 2021)
School children were vulnerable to had unhealthy snacked behavior due to their low knowledge and awareness in clean and healthy lived behavior. Even though there was a lot of data that shows unhealthy snacks for school children are sold not in the school canteen. To stimulate children's intelligence so that children could had good food and should achievements, smart acupressure was carried out, so that children were healthy in nutrition and brain. The purposed of this serviced was to seek to improved the health status of elementary school children through comprehensive promotive, preventive efforts and to increase student knowledge primary school. There was certainly very important to increased the awareness of school children about the importance of been aware of dangerous food snacked. This health education and smart acupressure trained was held in February 2020 at SDN Mlajah 01, and as a result the students (Afni, 2018)knew about the dangers of consumed food carelessly and the consequences if consumed such food, and smart acupressure trained could be carried out correctly by students of SDN Mlajah Bangkalan